Complement C1q Interacts With LRP1 Clusters II and IV Through a Site Close but Different From the Binding Site of Its C1r and C1s-Associated Proteases - Fouët, Guillaume; Gout, Evelyne; Wicker-Planquart, Catherine; Bally, Isabelle; De Nardis, Camilla; Dedieu, Stéphane; Chouquet, Anne; Gaboriaud, Christine; Thielens, Nicole M.; Kleman, Jean-Philippe; Rossi, Véronique (Frontiers in Immunology, 2020)
LRP1 is a large endocytic modular receptor that plays a crucial role in the scavenging of apoptotic material through binding to pattern-recognition molecules. It is a membrane anchored receptor of the LDL receptor family with 4 extracellular clusters of ligand binding modules called cysteine rich complement-type repeats that are involved in the interaction of LRP1 with its numerous ligands. Complement C1q was shown to interact with LRP1 and to be implicated in the phagocytosis of apoptotic cells. The present work aimed at exploring how these two large molecules interact at the molecular level using a dissection strategy. For that purpose, recombinant LRP1 clusters II, III and IV were produced in mammalian HEK293F cells and their binding properties were investigated. Clusters II and IV were found to interact specifically and efficiently with C1q with KDs in the nanomolar range. The use of truncated C1q fragments and recombinant mutated C1q allowed to localize more precisely the binding site for LRP1 on the collagen-like regions of C1q (CLRs), nearby the site that is implicated in the interaction with the cognate protease tetramer C1r2s2. This site could be a common anchorage for other ligands of C1q CLRs such as sulfated proteoglycans and Complement receptor type 1. The use of a cellular model, consisting in CHO LRP1-null cells transfected with full-length LRP1 or a cluster IV minireceptor (mini IV) confirmed that mini IV interacts with C1q at the cell membrane as well as full-length LRP1. Further cellular interaction studies finally highlighted that mini IV can endorse the full-length LRP1 binding efficiency for apoptotic cells and that C1q has no impact on this interaction.